Prevalence of Sepsis and Possible Severe Bacterial Infection among Neonates in Nepal - Shrestha, Gambhir; Mulmi, Rashmi; Joshi, Nibaran; Shrestha, Parashu Ram (Journal of Nepal Health Research Council, 2018)
Nepal lacks adequate data on the prevalence of sepsis and Possible Severe Bacterial Infection (PSBI) among neonates. Thus, this systematic review was designed to estimate the prevalence of neonatal sepsis and PSBI status in Nepal. We searched PubMed and Nepal Journal Online for relevant studies on PSBI and neonatal sepsis published from 2006 to 2016. The eligibility criteria included those studies done in Nepal, evaluating the prevalence of PSBI/neonatal sepsis with denominators as the population at risk that is either total live births or total cases evaluated. Altogether, four studies met the review criteria, out of which three were hospital-based and one community-based. There is a vast difference in prevalence rate between hospital-based (2-4%) and community-based (9%) studies. Two studies used haematological scoring system and blood culture to base their diagnosis; one used signs and symptoms for PSBI while the other did not mention the diagnostic criteria. This systematic review suggests that though neonatal sepsis poses a big problem, it lacks a significant number of related studies. There is a need to conduct a nationwide survey on the prevalence of sepsis and PSBI among neonates, which will help to develop health policy.